Pengaruh Pemahaman Perpajakan, Efektivitas Layanan, Dan Sanksi Terhadap Kepatuhan Membayar Pajak Kendaraan Di Kabupaten Tabanan - I Dewa Gede Nata Susila; Ni Komang Sumadi; I Made Endra Lesmana Putra (UNHI Press, 2025)
Taxes are a vital source of government revenue that support economic growth and development, both nationally and regionally. Motor vehicle tax, as part of regional taxation, significantly contributes to Regional Original Income (PAD), which is then allocated to finance development programs and public services. This study aims to analyze the effect of tax understanding, service effectiveness, and sanctions on motor vehicle taxpayer compliance. A quantitative approach was applied using a survey of 81 respondents selected through stratified random sampling based on the distribution of taxpayers across ten districts. Data were analyzed using multiple linear regression. Simultaneously, the three variables significantly affect taxpayer compliance. These results suggest that efforts to improve taxpayer compliance should emphasize tax education and enhancing service quality.